A multicenter quality improvement initiative on the impact of pharmacists' postdischarge follow-up to reduce medication-related acute care episodes. (21st January 2020) - Noh, Lydia; Heimerl, Kristina; Shane, Rita
Abstract: Purpose: This multicenter quality improvement initiative aims to measure and quantify pharmacists' impact on reducing medication-related acute care episodes (MACEs) for high-risk patients at an increased risk for readmission due to drug-related problems (DRPs). Methods: This was a prospective, multicenter quality improvement initiative conducted at 9 academic medical centers. Each participant implemented a standardized methodology for evaluating MACE likelihood to demonstrate the impact of pharmacist postdischarge follow-up (PDFU). The primary outcome was MACEs prevented, and the secondary outcome was DRPs identified and resolved by pharmacists. During PDFU, pharmacists were responsible for identification and resolution of DRPs, and cases were reviewed by physicians to confirm whether potential MACEs were prevented. Results: A total of 840 patients were contacted by 9 participating academic medical centers during a 6-week data collection period. Of these, 328 cases were identified as MACEs prevented during PDFU by pharmacists, and physician reviewers confirmed that pharmacist identification of DRPs during PDFU prevented 27.9% of readmissions. Pharmacist identified 959 DRPs, 2.8% (27) of which were identified as potentially life threatening. Potentially serious or significant DRPs made up 56.6% (543) of the DRPs, and 40.6% (389) were identified as having a low capacity for harm. Conclusion: The results demonstrate that PDFU of high-risk patients reduces DRPs and prevents MACEs based on physician confirmation. Implementation of MACE methodology provides health-system pharmacy departments the ability to demonstrate pharmacists' value in transitions of care and assist in expanding pharmacist services.